Predicting Placement in Residential Treatment in a Drug Court Program - Shaffer, Deborah Koetzle (Criminal justice policy review, 2025)
With a growing emphasis on alternatives to incarceration for high-risk/high-need individuals who use drugs or alcohol, there is an increased need for intensive treatment services in the community. The current study examines referrals to residential treatment in a drug court setting. Using a sample of 378 drug court participants, this study compares characteristics of drug court participants who received traditional drug court services and those who received residential services. Multivariable logistic regression model analyses indicate that drug of choice (i.e., heroin/opiate use), substance use severity (i.e., early onset of drug use at 15 years and below), and noncompliance (i.e., rearrests prior to referral) were significant predictors of referral to and placement in residential treatment, when controlling for demographic characteristics (i.e., age, race, gender). Research and policy implications are discussed.